2021
DOI: 10.1038/s43705-021-00016-0
|View full text |Cite
|
Sign up to set email alerts
|

Microscale tracking of coral-vibrio interactions

Abstract: To improve our understanding of coral infection and disease, it is important to study host-pathogen interactions at relevant spatio-temporal scales. Here, we provide a dynamic microscopic view of the interaction between a coral pathogen, Vibrio coralliilyticus and its coral host Pocillopora damicornis. This was achieved using a microfluidics-based system facilitating control over flow, light and temperature conditions. Combined with time-resolved biochemical and microbial analyses of the system exudates, this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 55 publications
2
12
0
Order By: Relevance
“…Several subsequent studies have successfully employed pES213-derived donor plasmids for the creation of stable GFP tags in A. fischeri ( 33 ) and the Vibrio spp. V. harveyi ( 18 , 34 ), V. parahaemolyticus ( 35 , 36 ), V. coralliilyticus ( 37 ), V. aestuarianus ( 22 ), and V. tapetis ( 38 ). However, a formal side-by-side comparison of conjugation methods and the acquired plasmid retention is needed to standardize these methods across different vibrios.…”
Section: Introductionmentioning
confidence: 99%
“…Several subsequent studies have successfully employed pES213-derived donor plasmids for the creation of stable GFP tags in A. fischeri ( 33 ) and the Vibrio spp. V. harveyi ( 18 , 34 ), V. parahaemolyticus ( 35 , 36 ), V. coralliilyticus ( 37 ), V. aestuarianus ( 22 ), and V. tapetis ( 38 ). However, a formal side-by-side comparison of conjugation methods and the acquired plasmid retention is needed to standardize these methods across different vibrios.…”
Section: Introductionmentioning
confidence: 99%
“…Coral holobionts harbor a complex consortium of microorganisms, including zooxanthellae, bacteria, archaea, fungi, viruses, and protists (Knowlton and Rohwer, 2003). Coral microbial flora has been attracting attention for their potentials to protect corals from environmental stresses and their relevance with coral hosts, such as defense against pathogens, promotion of coral health, development, nutrition-based symbioses, and environmental adaption (Krediet et al, 2013;Soffer et al, 2015;Lema et al, 2016;Yang et al, 2016;Zhou et al, 2017;Bernasconi et al, 2019;Babbin et al, 2021;Gavish et al, 2021;Kitamura et al, 2021). For example, the confirmation of anaerobic nitrogen metabolism in coral microorganisms sheds new light on coral and reef productivity (Babbin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Certner et al (2017) demonstrated that white-band disease (WBD) transmission can be facilitated through zooplankton ingestion following incubation in tissue homogenate from diseased corals. In a similar vein, Gavish et al (2021) utilized a microscale visualization system to observe colonization of Pocillopora damicornis by Vibrio coralliilyticus from ambient sea water, suggesting that ingestion may be a primary route of entry for the pathogen. Corals support their carbon and nutrient needs through the mutualistic relationship with their algal symbionts and through direct feeding.…”
Section: Introductionmentioning
confidence: 99%
“…Heterotrophy provides up to 35% of a healthy coral’s daily metabolic needs and up to 100% in bleached corals, largely by nighttime feeding on zooplankton (Houlbrèque & Ferrier-Pagès, 2009; Ferrier-Pagès et al, 2010). While Gavish et al (2021) demonstrates the viability of pathogen acquisition via direct ingestion of bacteria, preferential grazing of zooplankton, which are known to be colonized by bacteria (and Vibrio in particular [Erken et al, 2015]), may represent an important exploitable pathway for pathogenic microbes to gain entry to a coral host. We hypothesize that pathogen-colonized zooplankton may serve as a foodborne vector for disease transmission in uninjured corals.…”
Section: Introductionmentioning
confidence: 99%